2007
DOI: 10.2471/blt.06.031922
|View full text |Cite
|
Sign up to set email alerts
|

Trichomoniasis and bacterial vaginosis in pregnancy: inadequately managed with the syndromic approach

Abstract: Objective To measure the prevalence of Trichomonas vaginalis (TV) infection and bacterial vaginosis (BV) among pregnant women in Botswana, and to evaluate the syndromic approach and alternative management strategies for these conditions in pregnancy. Methods In a cross-sectional study, 703 antenatal care attendees were interviewed and examined, and specimens were collected to identify TV, BV, Candida species, Chlamydia trachomatis and Neisseria gonorrhoeae. Information on reproductive tract infections earlier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
2
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 34 publications
7
55
2
4
Order By: Relevance
“…This result is higher than the 3.9% observed in Jordan [29] and the 8% reported in pregnant woman in Botswana [30].In developing countries, including Sudan, diagnosis of cervical infections namely due to C. trachomatisis limited to the syndromic approach of relying on the appearance of vaginal discharge [31]. Due to the high prevalence of C. trachomatis infections in this study, routine diagnostic techniques such as the direct fluorescence test or polymerase chain reaction are needed in our hospitals.…”
Section: Discussioncontrasting
confidence: 53%
“…This result is higher than the 3.9% observed in Jordan [29] and the 8% reported in pregnant woman in Botswana [30].In developing countries, including Sudan, diagnosis of cervical infections namely due to C. trachomatisis limited to the syndromic approach of relying on the appearance of vaginal discharge [31]. Due to the high prevalence of C. trachomatis infections in this study, routine diagnostic techniques such as the direct fluorescence test or polymerase chain reaction are needed in our hospitals.…”
Section: Discussioncontrasting
confidence: 53%
“…15,16,17 The prevalence rates of BV among pregnant women vary from 6.4% to 38%. 18,19 The overall prevalence of BV by Gram stains Nugent scoring criteria in a study by Mengistie et al was 19.4%. 20 The studies done in India and Denmark showed the prevalence as 20.5% and 17%.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 50 % of women with Trichomonas vaginalis are asymptomatic (Swygard et al 2004, Romoren et al 2007, and the extent of the inflammatory responses to the parasite determines severity of the symptoms. There are reports of dysuria, lower abdominal discomfort, itchiness of the vagina, leucorrhea, and vaginal odor in some women (Schwebke and Burgess 2004).…”
Section: Clinical Manifestation In Humansmentioning
confidence: 99%